Casa da mulher cearense: estima de lugar e produção de mapas afetivos com as mulheres assistidas em Sobral/Ce - Paiva, Bruna Lopes (2024)
The present study is divided into two parts: the first addresses an article published in 2024, titled "The Importance of Public Policies to Combat Violence Against Women: A Look at the Casa da Mulher Cearense in Sobral/CE." It provides an explanation of the need to promote public policies for the prevention of violence against women, highlighting the public institution Casa da Mulher Cearense in Sobral/CE. For this analysis, the article presents data on violence against women in Brazil from 2022 to 2024, offering a snapshot of the reality in Ceará. Furthermore, it revisits the historical process in the country, citing major laws, government plans, and agreements that have consolidated and strengthened public policies for the protection of women in Brazil, and emphasizes the importance of public institutions such as the Casa da Mulher Cearense in Sobral/CE for protecting women’s lives. The second part of this study is original and seeks to understand the emotional dynamics of women assisted by the Casa da Mulher Cearense in Sobral/CE (CMCS), in relation to this institution, in an attempt to support the aspects arising from the person-environment relationship. It is based on the understanding that environments extend beyond physical structures, also encompassing symbolic aspects, including feelings, perceptions, emotions, and individuals' representations of certain places. Theoretically, the second part of this study is grounded in the categories of "Place Attachment," "Affective Maps," and "Affectivity," which are addressed by theorists of Environmental Psychology and Historical-Cultural Psychology. Methodologically, the study is qualitative in nature, and its data collection strategy involved the use of the Affective Map Generator Instrument. A specific portion of the population that accesses this institution was selected, with the inclusion criterion being women who participate in the Dance Group of the Casa da Mulher Cearense in Sobral/CE, and the exclusion criterion being women who do not participate in the Dance Group or, due to lack of interest, did not wish to participate in the research. The results presented affective images, indicating the prevalence of Place Attachment shown by the group (either enhancing or diminishing), considering that their experiences carry histories of violence. Finally, the study enables the visualization of the vulnerabilities, risks, and potential for overcoming the violence faced by women, encouraging a rethinking and stimulation of new professional practice strategies for the workers of the Casa da Mulher Cearense.